The Degree of Practice of the Strategies for Teaching Arabic Language by Teaching Staff Members in the Jordanian Universities - Bani Yasin, Mohammed Fawzi Ahmed (Arab Journal for Sciences and Research Publishing, 2016)
The aim of the study was to find out The Degree of Practice of the Strategies for Teaching Arabic Language by Teaching Staff Members in the Jordanian Universities. In order to achieve this, the researcher designed a questionnaire distributed to 100 faculty members, which consisted of three areas: theories, approaches and strategies. The results of the study in the field of theories, which included (4) theories, showed that the theory of "top to bottom" was ranked first, while the "social cultural theory" ranked last. The results of the study in the field of linguistic entries, which included (7) entries, that the "traditional" entry was ranked first, while the "syntactic and skillful" came in last. The strategy area, which included 20 strategies, showed results in three levels: high, medium and low. The strategy of the "lecture" at the high level was ranked first by (9.338%), while the self-learning strategy at the same level was ranked last (6.614%). At the intermediate level, the "exchange strategy" (6.42%), while the "micro-teaching strategy" at the same level ranked last (3.696%). At the low level, the "self-accountability strategy" ranked first with 2.918% "At the same level last place by (0.194%) .
Keywords: degree of practice; strategies for teaching Arabic